Squeak! - Davidson, Rose, 1989-; National Geographic Society (U.S.) (Washington, DC : National Geographic Kids, 2019)
Mice and rats may be the most famous rodents, but readers will discover the diverse--and maybe even adorable--world of little squeaking critters. From cavies and capybaras to jerboas and gerbils to pocket mice and porcupines, get ready for the rodents. Packed with weird-but-true facts and tons of animal info, this Level 3 Reader shows just how endearing rodents can be. Meet the adorable pika, fuzzy hamsters, and yes, even supersmart rats, and collect cool facts about these scurrying squeaky creatures. National Geographic Fact Readers feature the same expert-vetted running text as traditional readers--with a bonus of 100 fun facts sprinkled throughout! A fact roundup at the end of each book lets kids review what they've learned. (Plus, they can impress their friends with their animal expertise!)
25 cool facts about rodents -- Rodents rule -- Amazing abilities -- Wild rodents -- Furry friends -- 25 more facts about rodents -- Rodent facts roundup
Age 6-9.
K to Grade 3.
Keywords: Rodents -- Juvenile literature; Rodents